The Renaissance of Homeworking in Developed Economies - Lipsig-Mummé, Carla (Relations industrielles / Industrial Relations, 1983)
The purpose of this paper is to offer an analysis and overview of the causes and implications of the renaissance of homeworking in many industries in Western Europe, North America and Australia since the 1960's